The Implementation of Economic, Social and Cultural Rights in Canada: Between Utopia and Reality - Miriam Cohen; Martin-Olivier Dagenais (The Constitutional Court of the Republic of Indonesia, 2021)
Canada has been at the forefront of the recognition of human rights, including economic, social and cultural rights (ESC rights) in the international scene. As a party to the International Covenant on Economic, Social and Cultural Rights,1 Canada has, over the years, implemented in legislation and case-law some ESC rights such as the right to health, education and social welfare.While ESC rights were not explicitly identified in the Charter of Rights and Freedoms,2 which forms part of the Canadian Constitution, ESC rights in different forms have received some protection in the Canadian legal order. An analysis of the Canadian record with respect to ESC rights demonstrates the immense gap between a glorified image of Canada as an international human rights proponent (the ‘utopia’) and the actual implementation of internationally recognized human rights in Canada (the ‘reality’). As Canada is bound to face major transformational changes to its economy and social fabric in the years to come, the Courts will have to adapt quickly and efficiently to ensure a smooth transition. This paper overviews the evolution of the case-law on ESC rights in Canada in light of its international obligations, and suggests, the relevant ESC rights jurisprudence signals a disconnect with Canada’s international obligation ‘requiring progressive implementation to the maximum of available resources by all appropriate means.’